2020
DOI: 10.1111/jfpp.15115
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles, antioxidant, and phenolic contents of oils extracted from Acacia polyacantha and Azadirachta indica (Neem) seeds using green solvents

Abstract: The purpose of the present study was to evaluate the composition of fatty acids, antioxidant, and phenolic compounds in Acacia polyacantha and Azadirachta indica seed extracts for their potential uses in nutrition. Extractions of oil using several techniques (Soxhlet, ultrasound, and microwave) in several solvents were carried out and the oils were characterized. Total phenolic content ranged between 4.22 and 31.48 mg GAE/g. Antioxidant activity (CE50) ranged between 1.95 and 22.91 mg/ml. Oleic and linoleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
(60 reference statements)
0
14
1
Order By: Relevance
“…Only one paper (Banerji et al, 1988) has been found reporting such an extreme concentration of α-linolenic acid in Acacia s.l. (including Senegalia) seeds and is not in agreement with several reports (Gunstone et al, 1968;Jamal et al, 1987;Mustafa & El-Kamali, 2016;Tchinda et al, 2020) on the same species. Besides, the content of oil in Senegalia seed is marginal.…”
Section: Lipid Nutritional Valuescontrasting
confidence: 92%
See 2 more Smart Citations
“…Only one paper (Banerji et al, 1988) has been found reporting such an extreme concentration of α-linolenic acid in Acacia s.l. (including Senegalia) seeds and is not in agreement with several reports (Gunstone et al, 1968;Jamal et al, 1987;Mustafa & El-Kamali, 2016;Tchinda et al, 2020) on the same species. Besides, the content of oil in Senegalia seed is marginal.…”
Section: Lipid Nutritional Valuescontrasting
confidence: 92%
“…Senegalia seeds have been reported to contain phenolic acids (principally ellagic and vanillic acid), flavonoids ((epi)catechin and rutin), condensed tannins (830-2060 mg/100 g dm), cardiac glycosides, steroids, alkaloids, (hemolytic) saponins, phytate (1030-1528 mg/100 g dm), trypsin inhibitors (0.14-132 TIU/mg protein), lectins, amines, nonproteinogenic amino acids, and fatty acid epoxides (Babu & Subrahmanyam, 2010;Balogun & Fetuga, 1989;Barton et al, 1993;Evans et al, 1977Evans et al, , 1979Evans et al, , 1985Evans et al, , 1993Guissou et al, 2020;Hapner & Jermyn, 1981;Lee et al, 1977;Loganayaki et al, 2011;Odei-Addo et al, 2014;Prakash et al, 2001;Rajaram & Janardhanan, 1991;Shah et al, 1992;Sharma & Kaur, 2017;Sotelo et al, 1995;Tchinda et al, 2020;Thangavelu et al, 2015Thangavelu et al, , 2017Thangavelu et al, , 2020. Again, as it can be noted, there is limited research and details on the composition of Senegalia seeds' phytochemicals.…”
Section: Phytochemicals: Nutrients Bioactives or Antinutritional Fact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this result may be due to the fact that the phenolic compounds, as well as the other active compounds responsible for promoting AA in oil, are thermolabilbilities and can be degraded by the interactive effect between a long time and high temperature of Soxhlet extraction (Chanioti & Tzia, 2017). Tchinda et al (2021) and Mohammadpour et al (2019) also reported higher TPC content and AA in the oil obtained by the UAE compared to the Soxhlet extraction of Acacia polyacantha and Moringa peregrina seeds, respectively. In addition, although the C* ab of the oil obtained by the UAE has resulted in a slightly more opaque saturation than the oil of the Soxhlet, the advantage of a lower extraction time (10 min) can be considered in relation to the conventional method (8 h), evidencing the relevance of this process.…”
Section: Resultsmentioning
confidence: 92%
“…oil, are thermolabilbilities and can be degraded by the interactive effect between a long time and high temperature of Soxhlet extraction(Chanioti & Tzia, 2017) Tchinda et al (2021). and Mohammadpour et al (2019) also reported higher TPC content and AA in the oil obtained by the UAE compared to the Soxhlet extraction of Acacia polyacantha and Moringa peregrina seeds, respectively.…”
mentioning
confidence: 99%